Planejamento e distribuição espacial de atributos químicos do solo e produtividade da macadâmia - Paris, Jaqueline Orlandi (2018)
Knowledge of the spatial variability of soil chemical attributes and productivity through the use of geostatistics becomes a tool to aid in the management of macadamia walnut, controlling its production system. The objective of this study was to determine the spatial variability of soil chemical attributes, as well as their spatial correlation with productivity, as well as to delimit zones of agricultural management and to propose a soil sampling methodology that best adjusts to the soil system conditions. management. The experiment was conducted in a macadamia plantation, HAES 344 variety, aged 20 years, planted at a spacing of 8.0 x 5.0 m (250 plants ha1 ), under a micro-sprinkler irrigation system in the municipality of São Mateus - ES. In the experimental area with dimensions of 144 x 140 m (20,160 m2 ), a mesh with 100 sample points was demarcated. At each sampling point, productivity and soil samples were collected at 0.0-0.20 m depth for the chemical analysis of phosphorus, potassium, calcium, magnesium, iron, copper, zinc, manganese, organic matter, sodium, active acidity, potential acidity, aluminum, cation exchange capacity at pH 7.0 and base saturation. The productivity of each macadamia plant was performed by harvesting the fruits in the crown of the plant, delimited by the central division between plants in the row and between planting lines. Data were submitted to descriptive, multivariate and geostatistical statistical analysis. We verified a spatial dependence structure for all variables under study, fitting the spherical model. The analysis of isoline maps allowed the delineation of 3 management zones for the application of differentiated limestone. The statistical parameters allowed to establish ix the adequate number of samples to analyze the attributes studied that ranged from 1 to 18 sample points. The area under study presented a central tendency of better conditions for the culture due to higher levels of calcium, magnesium, zinc, pH and low H+Al content. The association of the definition of management zones, number of samples and spatial variability of soil attributes can be used to improve the efficiency of application of agricultural inputs, and to the development of sampling strategies that minimize costs within an error known and tolerable. The integration between hierarchical clustering analysis and Pearson's linear correlation of plant morphometrics, soil attributes and yield was effective in determining similar and distinct groups in a macadamia crop.